Translingual and Transnational Graduate Education in Rhetoric and Composition - Kilfoil, Carrie Byars; Bou Ayash, Nancy (Book collections on Project MUSE., 2023)
"This book systematically investigates the implications of composition studies' changing terminological and ideological landscape around language and nation for the education and professionalization of future writing teachers and specialists. Incorporating these theories into graduate pedagogy and curricular structures in composition is necessary to shape professional practices in the field long term"--